Estrés laboral y sus consecuencias en la salud que afectan el rendimiento (2020)
Work stress is defined as the emotional and/or physical reaction that the human being has in situations that surround him; in addition it can also be defined as a physiological and psychological response of the worker. Studies on job stress have revealed that lately this problem or condition has greatly affected people who work as workers; since the consequences of suffering stress from work are sufficient, they are also serious and in some cases difficult to manage. Currently stress is a fairly important factor at the social level, since it manifests itself in people when it comes to having excessive or controlled loads that go beyond the capacities they suffer. Occupational stress can be the cause of many diseases, from physical health problems such as cardiovascular disorders, digestive system problems, and dermatological disorders, among others; to mental health problems, anxiety, depression, insomnia, Burnout syndrome and many more. All these pathologies experience that work stress is not an issue that should be ignored, overlooked, or even judged, since as was specifically the consequences of this situation that currently occurs in almost all people who carry out child labor. Be very careful, because if it can be avoided they can cause fatal damage to humans or even cause death.